SOME ACCOUNTING LIMITATIONS OF STATEMENT INTERPRETATION. - Morrison, Lloyd F. (The Accounting Review, 1952)
Abstract This article presents a paper that was undertaken to examine an aspect of accounting that is currently receiving much attention, accounting controls. It is not a new topic for it seems that most of present day methods and procedures have developed to serve the purposes of control. By referring to this branch of accounting as accountability it is intended to lend the sanction of acceptance and to broaden the scope so that some of the ultimate aspects of accountability may be examined. Again let it be noted that accounting is a tool of management but that is not the sole function of accounting. The importance of maintaining the integrity of the methods and procedures required for purposes of accountability should not be overlooked in the rush to change the statements to take into account general variations in the economy. Financial statements of a business enterprise do not reflect the economic condition of the enterprise, but from these statements a skilled analyst may draw information, which will assist him in arriving at conclusions regarding the economic condition of the enterprise. Although statements do not supply all of the information necessary to form a complete picture of the economic condition of an enterprise, statements are portrayals of economic facts and activities selected and arranged to serve practical needs of interested parties.